The The rooftop solar power plant of electrical engineering department of medan state polytechnic with the internet of things - Suprianto; Afritha Amelia; Cholish; Abdullah (Institute of Computer Science (IOCS), 2023)
The use of renewable energy for electricity generation in Indonesia and the world continues to increase because it is environmentally friendly and does not depend on fossil fuels. Research on rooftop solar power plants at the Medan State Polytechnic Building, Department of Electrical Engineering with internet of things aims to implement rooftop solar power plants and determine the performance of rooftop solar power plants in serving electrical loads by controlling electrical loads using the Internet of things. The contribution of this research provides an academic reference for the effective design of a rooftop solar power plant electrical system and savings on electricity bills, especially in the Electrical Engineering Department of the Medan State Polytechnic. The method used in this study is an experimental method, namely collecting data from measurement results, then conducting studies and analysis. The equipment used is NodeMCU ESP 8266, 3300wp photovoltaic module, PZEM 004T sensor, Triac BT 136, inverter, RTC DS 3231, contactor, electricity meter, temperature and light intensity meter, battery system, control panel and other supporting equipment. the internet of things as a load controller from a solar power plant can effectively contribute to saving electricity consumption because reluctance to turn off lights that are not used doesn't make sense because they can be controlled remotely or in close proximity practically using a cellphone via the blynk application. Full load is applied to the solar power plant by activating the four lighting load group buttons on the Blynk IoT app. The average battery voltage at loading is 51.6 volts from a normal battery voltage of 48 volts with the lowest battery voltage of 48.5 volts and the highest battery voltage of 54.31 volts. This rooftop solar power plant in Building C of the Medan State Polytechnic is capable of serving a load of 685 watts for a fixed load that is installed for 11 hours of loading.